Comparative study between the alkaline phosphatase and gammaglutamyl transpeptidase on the diagnosis of hepatic metastases. - Larre Borges, Alba; Osinaga, Eduardo; Sanguinetti, Julio; Cayota, Alfonso; López, Ana; Larre Borges (h), Uruguay (Cirugía del Uruguay, 1983)
COMPARATIVE STUDY BETWEEN THE ALKA LINE PHOSPH ATASE AND GAMM AGL UT AMYL TRAN SPEPTIDASE ON THE DIAGNOSISOFHEPATICMETASTASES. In order to evaluate the utility on the diagnosis of the hepatic metas tases, the authors evaluated in 48 patients with digestive carcinomas, the activity of the Alkaline Phosphatase (FA) and the Gamma Glutamil Transpeptidase (GGT). lt was an study preoperatory, prospective and blind. Evaluated statistically the GGT was a superior test than the FA in the diagnosys of hepatic metastases, specially for its better sensitivity. Both enzymes showed a higher pr edktive value in the hepatic metastases. than in assure its existence.